Intellectual capital and organisational performance in Malaysian knowledge-intensive SMEs - Khalique M.; Bontis N.; Bin Shaari J.A.N.; Yaacob M.R.; Ngah R. (Inderscience Enterprises Ltd., 2024)
Indexed by Scopus/ERA